The Identification of Optimal Frequency for Ultrasonic Transducers in Concrete-Defect Detection using COMSOL® Simulator - Jamal Mohamad, Farah Aina; Anita Ahmad; Ruzairi Abdul Rahim; Sallehuddin Ibrahim; Juliza Jamaludin; Noorhazirah Sunar (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Ultrasonic testing for concrete evaluation is a non-destructive method that uses high-frequency acoustic waves to identify internal defects in concrete structures. This study aims to determine the optimal frequency for ultrasonic transducers in detecting defects in concrete structures. Simulations were conducted using COMSOL Multiphysics® software. The research involves designing, simulating, and analyzing a concrete model with various defects to evaluate the performance of different ultrasonic frequencies. A two-dimensional (2-D) concrete model was simulated, with three different types of defects introduced to assess their impact on the arrival time of ultrasonic signals. The simulation integrated pressure acoustics, solid mechanics, electrostatics, and electric circuit modules, with precisely defined material properties and meshing parameters. Results indicated that frequencies of 200 kHz and 500 kHz showed the highest sensitivity to defects. However, 200 kHz was identified as the optimal frequency due to its balance between sensitivity and energy loss. This frequency effectively distinguished individual defects and represents a reliable method for defect detection in concrete structures.